Et forbund af celler. Om krop, køn og identitet i ung dansk poesi - Mønster, Louise (Passage - Tidsskrift for litteratur og kritik, 2013)
Juul, Moestrup og Olsen danner ligeledes optakt i Louise Mønsters “Et forbund af celler. Om krop, køn og identitet i ung dansk poesi”. I denne artikel diskuteres det, hvordan den nyeste poesi med navne som Olga Ravn, Christina Hagen, Amalie Smith og Asta Olivia Nordenhof er optaget af krop, køn og identitet, og det vises, at forfatternes utraditionelle tilgange til disse emner går hånd i hånd med en radikal eksperimenteren med poesiens udtryksformer og grænser. Louise Mønster: “A Union of Cells. Body, Gender, and Identity in Young Danish Poetry” In contemporary Danish poetry body, gender and identity have become key issues. This article discusses the way Danish authors such as Ursula Andkjær Olsen, Mette Moestrup, Olga Ravn, Christina Hagen, Amalie Smith, and Asta Olivia Nordenhof deal with these themes, and argues that there is a strong tendency in new Danish poetry to break off from tradition. This is obvious, not only when the significance of body and materiality is stressed instead of the soul, and the concepts of male and female are transformed into more fluid categories. There is also a remarkable tendency to decompose genres, and so the article points out that the thematic focus on body, gender and identity seems to go along with a radical experimentation with poetic expressions and limits.